Discourse, pragmatic, and textual analysis of the body in Sunni Islam: Ritual purity, childbirth, and the interpretation of religious practice - Al‑Hasan Ibrahim, Yahya Muhammad Al‑Amin (Research Journal in Advanced Humanities, 2026)
States of uterine bleeding occupy a decisive place in Muslim ritual life because they reorganize obligations of prayer and fasting, shape norms of conjugal intimacy, and affect family‑law timelines. This article offers a religious‑studies reading of a classical juristic problem that remains pastorally urgent: how Sunni legal traditions differentiate between menstruation (ḥayḍ), postpartum bleeding (nifās), and the discharge or bleeding that can accompany the onset of labor (often termed al‑hādī). Rather than treating the topic as a purely technical catalogue of rulings, the study analyzes the evidentiary grammar by which jurists classify bodily signs—temporal thresholds, causal attributions, descriptive markers, and a woman’s established habit (ʿādah)—and shows how these semiotic choices generate divergent ritual consequences. Drawing on representative discussions across the four Sunni schools and on modern scholarship on ritual purity and embodied religion, the paper argues that the disputed status of pre‑labor discharge is best understood as a difference in evidentiary thresholds and in the legal semiotics of childbirth (event versus process), not merely as terminological disagreement. The conclusion proposes a purpose‑sensitive framework for navigating marginal cases that respects juristic pluralism while prioritizing certainty, harm prevention, and pastoral clarity in contemporary settings where biomedical categories and digital fatwā economies reshape how Muslims learn and practice.